Associations and democracy in Algeria. Issue 2 (23rd February 2017) - Northey, Jessica Ayesha
ABSTRACT: What role does associational activism play in political life in the Middle East and North Africa? Have associations been largely co-opted, thus reinforcing authoritarian governance? Or are they part of drawn out democratization processes, emerging over the last two decades, exploding during the Arab Spring? Divergences in responses to these questions have been striking. From initial optimism about the potential of associations to contribute to democratization, much recent literature has been increasingly pessimistic, framing associations as part of the problem of failed political transformations. Algeria, in particular, despite minimal donor funding, has seen a surge in associations over the last 20 years. Yet, these 93, 000 new associations have come under scrutiny. Building on extensive fieldwork, this article explores Algerian associations at grass-roots level, after the decade of violence in the 1990s. It analyses how associations challenged the state during the Arab Spring, how they question historical state narratives and challenge government policies. Despite political and structural obstacles, it is found that Algerian civic associations do not inhibit democratic society, indeed they enable it, not necessarily as transformative actors, but as meaningful democratic agents pushing for reform.